Engaging STEM students from rural areas emerging research and opportunities - Rogers, Reenay R. H. 1965-; Sun, Yan 1972 June 10- (IGI Global, 2019)
"This book provides a research-based comprehensive framework for successful recruitment, retention, and support of minority STEM undergraduate majors from rural areas. It also present research for addressing the critical shortage of minorities in professional STEM fields through outreach activities with rural K-12 students and teachers to encourage enrollment growth in science, math, and technology degree programs"--